Reconstitution of CD8 T Cells Protective against Cytomegalovirus in a Mouse Model of Hematopoietic Cell Transplantation: Dynamics and Inessentiality of Epitope Immunodominance - Holtappels, Rafaela; Lemmermann, Niels A. W.; Podlech, Jürgen; Ebert, Stefan; Reddehase, Matthias J. (Frontiers in Immunology, 2016)
Successful reconstitution of cytomegalovirus (CMV)-specific CD8+ T cells by hematopoietic cell transplantation (HCT) gives a favorable prognosis for the control of CMV reactivation and prevention of CMV disease after hematoablative therapy of hematopoietic malignancies. In the transient immunocompromised state after HCT, pre-emptive cytoimmunotherapy with viral epitope-specific effector or memory CD8+ T cells is a promising option to speed up antiviral control. Despite high-coding capacity of CMVs and a broad CD8+ T-cell response on the population level, which reflects polymorphism in major histocompatibility complex class-I (MHC-I) glycoproteins, the response in terms of quantity of CD8+ T cells in any individual is directed against a limited set of CMV-encoded epitopes selected for presentation by the private repertoire of MHC-I molecules. Such epitopes are known as ‘immunodominant’ epitopes (IDEs). Besides host immunogenetics, genetic variance in CMV strains harbored as latent viruses by an individual HCT recipient can also determine the set of IDEs, which complicates a ‘personalized immunotherapy’. It is therefore an important question if IDE-specific CD8+ T-cell reconstitution after HCT is critical or dispensable for antiviral control. As viruses with targeted mutations of IDEs cannot be experimentally tested in HCT patients, we employed the well-established mouse model of HCT. Notably, control of murine CMV (mCMV) after HCT was comparably efficient for IDE-deletion mutant mCMV-Δ4IDE and the corresponding IDE-expressing revertant virus mCMV-Δ4IDE-rev. Thus, antigenicity-loss mutations in IDEs do not result in loss-of-function of a polyclonal CD8+ T-cell population. Although IDE deletion was not associated with global changes in the response to non-IDE epitopes, the collective of non- IDE-specific CD8+ T-cells infiltrates infected tissue and confines infection within nodular inflammatory foci (NIF). We conclude from the model, and predict also for human CMV, that there is no need to exclusively aim for IDE-specific immunoreconstitution.